Metode Penafsiran Abdurrahman bin Nasir as-Sa’di dalam Kitab Taisir al-Karim ar-Rahman fi Tafsir Kalam al-Mannan pada Juz 30 - Muhammad Hasan Ali; Okky Octaviana; Eni Zulaiha (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The Qur'an is relevant at all times and places. However, as time progresses, many new problems arise in life and demand to be resolved immediately. This makes tafsir scholars rack their brains to answer these new problems with the special methods they use in interpreting the Qur'an. This research aims to determine the special method of interpretation used by Abdurrahman bin Nasir as-Sa'di in his tafsir work called Taisir al-Karim ar-Rahman fi Tafsir Kalam al-Mannan. The method used in this research is qualitative with a library research approach. As a result, the author found that Tafsir as-Sa'di uses the tafsir al-ra’yu source. Then in terms of general methods, Tafsir as-Sa'di uses the ijmali method which can be seen from its global and practical interpretation. Meanwhile, the special method used by as-Sa'di in his interpretation consists of things that are characteristic of this interpretation, thereby distinguishing it from other works of interpretation. The conclusion is that As-Sa'di made this tafsir to help scholars and make it easier for explorers of knowledge to understand the Al-Qur'an, therefore he made this tafsir in simple language, but still paying attention to the context, so that guidance, values pure, and the moral messages contained in the verses of the Qur'an can reach the heart and have a good impact in terms of improving worship of Allah SWT.